2020
DOI: 10.3389/fphar.2020.00809
|View full text |Cite
|
Sign up to set email alerts
|

Gehua Jiecheng Decoction Inhibits Diethylnitrosamine-Induced Hepatocellular Carcinoma in Mice by Improving Tumor Immunosuppression Microenvironment

Abstract: Gehua Jiecheng Decoction (GHJCD), a famous traditional Chinese medicine, has been used in the prevention and treatment of precancerous lesion of liver cancer, but its active mechanism has not been reported. This study aimed to evaluate the therapeutic effect of GHJCD on diethylnitrosamine (DEN)-induced hepatocellular carcinoma (HCC) in mice and the mechanism of this effect. We found that GHJCD effectively inhibited the occurrence of liver cancer and reduced the tumor area. The ratio of regulatory cells (Tregs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Furthermore, it has developed a mouse model (DEN/CCL4) with a high tumor HCC incidence and low death rate that may be used in a short time (8 weeks). For the long duration of 44 weeks of the DENinduced HCC model, a huge number of cancer nodules on the surface of the liver and ROS generation were observed (Cheng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has developed a mouse model (DEN/CCL4) with a high tumor HCC incidence and low death rate that may be used in a short time (8 weeks). For the long duration of 44 weeks of the DENinduced HCC model, a huge number of cancer nodules on the surface of the liver and ROS generation were observed (Cheng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…An inflammatory microenvironment generated by prolonged inflammatory cells and factors may also transform into an immunosuppressive microenvironment, thereby promoting angiogenesis and tumor progression. Immunotherapy is a novel and efficient tumor therapy (Cheng et al, 2020). Also, developing new therapeutics that target cell cycle and apoptosis dysregulation, inflammation, and fibrogenesis is crucial (Galicia-Moreno et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The famous Chinese medicine Gehua Jiecheng Decoction can inhibit the expression of CCL-2 in the liver while effectively inhibiting the development of tumor cells and reducing the tumor area. In addition, the expression of inflammatory factors and angiogenesis factors in the tumor is also reduced to varying degrees to antagonize the immunosuppressive effect of the liver cancer microenvironment ( 121 ). There is also evidence that blocking CCL-2 can promote TME recovery from inhibition ( 122 ).…”
Section: The Value Of Tls For Phc Treatmentmentioning
confidence: 99%
“…Initially, our research group focused on studying the sobering and liver-protective effects of Gehua jiecheng fang and found that these plants also possess anticancer properties. Among them, PF is the primary component, and there is literature supporting its use in HCC care (Cheng et al, 2020). The effect of Gehua jiecheng fang on excessive drinking is detailed in PiWeiLun (Chen et al, 2023).…”
Section: Introductionmentioning
confidence: 99%